Disruption of abscisic acid signaling constitutively activates Arabidopsis resistance to the necrotrophic fungus Plectosphaerella cucumerina - Sánchez Vallet, Andrea (2012)
Plant resistance to necrotrophic fungi is regulated by a complex set of signaling pathways that includes those mediated by the hormones salicylic acid (SA), ethylene (ET), jasmonic acid (JA), and abscisic acid (ABA). The role of ABA in plant resistance remains controversial, as positive and negative regulatory functions have been described depending on the plant-pathogen interaction analyzed. Here, we show that ABA signaling negatively regulates Arabidopsis (Arabidopsis thaliana) resistance to the necrotrophic fungus Plectosphaerella cucumerina. Arabidopsis plants impaired in ABA biosynthesis, such as the aba1-6 mutant, or in ABA signaling, like the quadruple pyr/pyl mutant (pyr1pyl1pyl2pyl4), were more resistant to P. cucumerina than wild-type plants. In contrast, the hab1-1abi1-2abi2-2 mutant impaired in three phosphatases that negatively regulate ABA signaling displayed an enhanced susceptibility phenotype to this fungus. Comparative transcriptomic analyses of aba1-6 and wild-type plants revealed that the ABA pathway negatively regulates defense genes, many of which are controlled by the SA, JA, or ET pathway. In line with these data, we found that aba1-6 resistance to P. cucumerina was partially compromised when the SA, JA, or ET pathway was disrupted in this mutant. Additionally, in the aba1-6 plants, some genes encoding cell wall-related proteins were misregulated. Fourier transform infrared spectroscopy and biochemical analyses of cell walls from aba1-6 and wild-type plants revealed significant differences in their Fourier transform infrared spectratypes and uronic acid and cellulose contents. All these data suggest that ABA signaling has a complex function in Arabidopsis basal resistance, negatively regulating SA/JA/ET- mediated resistance to necrotrophic fungi.